User consent acquisition system for Japanese Shibboleth-based academic federation (GakuNin). (10th October 2011) - Orawiwattanakul, Tananun; Yamaji, Kazutsuna; Nakamura, Motonori; Kataoka, Toshiyuki; Sonehara, Noboru
Shibboleth provides a federated single sign-on and an attribute exchange framework through its use of the security assertion markup language (SAML). One of major challenges for Shibboleth is the release of the user's information from an identity provider (IdP) to the service provider (SP) without prior consent of the user, and this may not comply with the privacy laws in some countries. This paper presents the requirements of a user consent acquisition system (UCAS) and a discussion on the existing UCASs for utilising GakuNin (Japanese academic federation) and the UCAS that we developed and call uApprove.jp. uApprove.jp is an extension of uApprove to enable users to control the release of optional attributes (user-attribute-filter) and to re-request the user consent if his/her information has changed (attribute-value check).